Clinical, Pathological, Treatment Pattern and Post-management Follow-up Features of Differentiated Thyroid Carcinoma (DTC) in a Tertiary Level Health Care Center of Bangladesh - Ahmed, Parvez; Ghosh, Subrata; Ahsan, Mostafa Shamim; Begum, Nasrin; Hossain, Mosharruf; Hosen, MM Arif (Medicine Today, 2020)
Introduction: This study evaluates clinical, pathological, treatment pattern and post-management follow-up features of differentiated thyroid carcinoma affected patients who had attended Rajshahi Medical College Hospital as well as private clinics and then Institute of Nuclear Medicine & Allied Sciences, Rajshahi for primary surgical management and post-operative radioiodine ablation therapy respectively. Materials and Methods: It is a retrospective study. Clinico-pathological, treatment and post-management follow-up features of 254 patients of histologically proved differentiated thyroid carcinoma (DTC) were recorded from their ultrasonography report, pre-operative cytology, operation note, post-operative histopathology and radioiodine ablation therapy related follow-up book between 2011 and 2015 and analyzed using statistical software IBM SPSS v. 16. Results: Among the sample (n=254), 211 (83 %) were female and 43 (17 %) were male. Mean age group was 30-39 years. In relation to FNAC findings of thyroid nodules among this study sample (n=254), 223 (88%) had malignant cytology, 16 (6%) had borderline cytology and 15 (6%) had benign cytology. Regarding the histopathological findings of thyroid nodules, 241 (95 %) had papillary carcinoma and 13 (5 %) had follicular carcinoma. Regarding radioiodine ablation dose, 198 (78%) had been given 138 millicurie (5.1 gigabecquerel) and 56 (22%) had been given 178 millicurie (6.6 gigabecquerel). Conclusion: Early and successful management of differentiated thyroid carcinoma is required to practice widely and equitably in order to significantly reduce mortality and morbidity related to such conditions. Medicine Today 2020 Vol.32(1): 25-28